Structural and Electronic Effects of Multiligand Coordination in a Single Transition Metal Complex a Study in Organic Reaction Catalysis - Samar Sabah Mohammed (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
The modulation of the structures and electronic properties of transition metal complexes by multi-ligands coordination has been widely exploited to enhance the catalytic efficiency in organic transformations. Here, we present synthesis, characterization, and catalytic performance of Cu(II), Ni(II) and Pd(II) complexes of multidentate ligands- EDTA, 1,10-phenanthroline and N-heterocyclic carbenes (NHCs). The Pd-NHC complex displayed the high catalytic activity for hydrogenation as well as small-molecule activation, up to 450 h⁻¹ of turnover frequency (TOF) and total conversion of styrene to ethylbenzene at room temperature, and is higher efficient than Cu-EDTA (TOF =120 h⁻¹), Ni-Phen (TOF= 85 h⁻¹). The DFT calculation with Pd-NHC system showed that the small HOMO-LUMO gap (3.2 eV) and the short Pd–C bond (1.95 Å) of Pd-NHC, which could facilitate the transfer of the growth species, contributed to the low energy of activation (28 kJ/mol). Mathematical model also discussed its high catalytic activity (TOF/Ea = 16.07 h⁻¹·kJ⁻¹·mol) due to the strong σ-donor ligands and proper geometry. These findings underscore the influence of ligand architecture to secure transition states and modulate electron density in designing efficient sustainable catalysis that is industrially relevant.